2021
DOI: 10.54113/j.sust.2021.000005
|View full text |Cite
|
Sign up to set email alerts
|

Research on dynamic characteristics test of wooden floor structure for gymnasium

Abstract: In order to better evaluate the structural performance of the wooden floor used in the gymnasium and realize the structural optimization design, this research considered two gymnasium’s floors in Nanjing as the research object and used the transient excitation method to test the natural frequency and damping ratio parameters of the three types of floor structures. The results showed that three kinds of floor structures all meet the requirements of building comfort; under the premise that the types and specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 3 publications
0
22
0
Order By: Relevance
“…The physical methods include drying treatment, alkali treatment, and electric treatment, whilst the chemical methods include acylation of lignocellulosic, etherification, graft etc. Wood can be treated to broaden its application scope [ 28 ] in addition to use in building construction [ 29 ]. Wood can be used as a building material for multistorey buildings, where the structural configuration can be optimized for seismic design [ 30 ].…”
Section: Influence Of the Raw Materialsmentioning
confidence: 99%
“…The physical methods include drying treatment, alkali treatment, and electric treatment, whilst the chemical methods include acylation of lignocellulosic, etherification, graft etc. Wood can be treated to broaden its application scope [ 28 ] in addition to use in building construction [ 29 ]. Wood can be used as a building material for multistorey buildings, where the structural configuration can be optimized for seismic design [ 30 ].…”
Section: Influence Of the Raw Materialsmentioning
confidence: 99%
“…Studies have shown that the composition of straw is similar to that of bamboo [61][62][63][64] and wood [65,66]. Therefore, it can be considered as an alternative raw material for wood and bamboo [67][68][69].…”
Section: Straw-based Panelsmentioning
confidence: 99%
“…where E is the elastic modulus of the specimen (Pa); ρ is the air-dry density of the specimen (kg/m -3 ); f1 is the first-order bending frequency of the specimen (Hz); L is the specimen length (m); and h is the specimen thickness (m) (Wang et al 2014(Wang et al , 2015(Wang et al , 2018Zhou et al 2021). The shear modulus was calculated according to Eq.…”
Section: Experimental Dynamic Testing and Quality Grading Of Elastic ...mentioning
confidence: 99%